2021
DOI: 10.3390/machines9120314
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Abrasive Belt Wear Based on BP Neural Network

Abstract: Abrasive belt grinding is the key technology in high-end precision manufacturing field, but the working condition of abrasive particles on the surface of the belt will directly affect the quality and efficiency during processing. Aiming at the problem of the inability to monitor the wearing status of abrasive belt in real-time during the grinding process, and the challenge of time-consuming control while shutdown for detection, this paper proposes a method for predicating the wear of abrasive belt while the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As one of the current mainstream research directions, intelligent algorithms are widely used in all walks of life with their characteristics including their multi-quantization of processing information, high prediction accuracy, and ability to find efficient solutions to complex problems. The research of scholars on intelligent algorithms has focused on analyzing prediction theory, model establishment, and algorithm optimization [40][41][42]. Common prediction models include the discrete choice model (DCM), support vector machines (SVMs), decision tree (DT), and the ANN.…”
Section: Based On Intelligent Algorithmic Modelsmentioning
confidence: 99%
“…As one of the current mainstream research directions, intelligent algorithms are widely used in all walks of life with their characteristics including their multi-quantization of processing information, high prediction accuracy, and ability to find efficient solutions to complex problems. The research of scholars on intelligent algorithms has focused on analyzing prediction theory, model establishment, and algorithm optimization [40][41][42]. Common prediction models include the discrete choice model (DCM), support vector machines (SVMs), decision tree (DT), and the ANN.…”
Section: Based On Intelligent Algorithmic Modelsmentioning
confidence: 99%
“…Firstly, neural networks can model complex relationships owing to their substantial nonlinear fitting ability, allowing them to capture intricate relationships between input and output parameters. This capability enables the establishment of mapping relationships that explicit mathematical models cannot construct [16]. Secondly, neural networks exhibit strong generalization ability, providing reliable prediction results even in the face of unknown working conditions and parameter combinations by generalizing from training samples.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other studies, Sun et al [ 12 ] used 3700 records of images as a dataset to train a ResNet-based CNN from scratch, and the dataset must go through image pre-processing as well. Most of the studies [ 25 , 26 ] on the degree of wear of abrasive belts have mainly focused on the conditions of the abrasive belt or the grinding acoustic signal of the abrasive belts [ 27 , 28 ], while the present research concentrates on the surface texture of the workpieces after grinding. As summarized by Xie et al [ 8 ] and reported in the introduction of the manuscript, most defect detection techniques focus on local defects, not on tonality defects.…”
Section: Introductionmentioning
confidence: 99%